Adrenaline Improves Platelet Reactivity in Ticagrelor-Treated Healthy Volunteers - Singh, Sukhi; Damén, Tor; Nygren, Andreas; Shams Hakimi, Caroline; Ramström, Sofia; Dellborg, Mikael; Lindahl, Tomas L.; Hesse, Camilla; Jeppsson, Anders (Thrombosis and Haemostasis, 2019)
Background Administration of agents that enhance platelet reactivity may reduce the perioperative bleeding risk in patients treated with the adenosine diphosphate (ADP)-receptor antagonist ticagrelor. Adrenaline potentiates ADP-induced aggregation and activation in blood samples from ticagrelor-treated patients, but it has not previously been evaluated in vivo.Methods Ten healthy male subjects were included in an interventional study. A loading dose of ticagrelor (180 mg) was administered, followed 2 hours later by a gradually increased intravenous adrenaline infusion (0.01, 0.05, 0.10 and 0.15 µg/kg/min; 15 minutes at each step). Blood pressure, heart rate, platelet aggregation (impedance aggregometry), platelet activation (flow cytometry), clot formation (rotational thromboelastometry) and adrenaline plasma concentration were determined before and after ticagrelor administration and at the end of each adrenaline step.Results Infusion of adrenaline increased ADP-induced aggregation at all doses above 0.01 µg/kg/min. The aggregation increased from median 17 (25−75th percentiles: 14−31) to 25 (21−34) aggregation units (p = 0.012) at 0.10 µg/kg/min. Adrenaline infusion also increased ADP-induced fibrinogen receptor activation (from 29 [22–35] to 46 [38−57%]) and P-selectin expression (from 3.7 [3.0−4.3] to 7.7 [4.7−8.6%]), both p = 0.012. Adrenaline infusion reduced clot formation time (97 [89−110] to 83 [76−90] seconds, p = 0.008) and increased maximum clot firmness (59 [57−60] to 62 [61−64] mm, p = 0.007).Conclusion Infusion of adrenaline at clinically relevant doses improves in vivo platelet reactivity and clot formation in ticagrelor-treated subjects. Adrenaline could thus potentially be used to prevent perioperative bleeding complications in ticagrelor-treated patients. Studies in patients are necessary to determine the clinical importance of our observations.Trial Registry Number ClinicalTrials.gov NCT03441412.
Keywords: adrenaline; ticagrelor; platelet function; flow cytometry; impedance aggregometry